Polishing composition for silicon substrates

The polishing liquid composition for silicon substrates, using silica particles and a specific amino group-containing polymer, enhances polishing rate and storage stability by reducing electrostatic repulsion, thus overcoming aggregation and filter clogging issues.

JP7599502B2Active Publication Date: 2024-12-13KAO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022555235
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-09
Publication Date
2024-12-13
Estimated Expiration
2040-10-09

AI Technical Summary

Technical Problem

Existing polishing liquid compositions for silicon substrates face issues such as low polishing rate, silica particle aggregation leading to surface defects, filter clogging, and poor storage stability, particularly in concentrated form.

Method used

A polishing liquid composition for silicon substrates containing silica particles and an amino group-containing water-soluble polymer with a pKa of 5 or more and 8.5 or less, maintained at a pH of 8.5 to 14, which reduces electrostatic repulsion and aggregation, enhancing both polishing rate and storage stability.

Benefits of technology

The composition achieves high-speed polishing with improved surface quality and storage stability, addressing the limitations of previous compositions by suppressing silica particle aggregation and maintaining dispersion stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599502000001
    Figure 0007599502000001
  • Figure 0007599502000002
    Figure 0007599502000002
  • Figure 0007599502000003
    Figure 0007599502000003
Patent Text Reader

Abstract

One aspect provides a polishing liquid composition which is for a silicon substrate and with which improvements in the polishing speed and storage stability of a concentrate can both be achieved. In one aspect, the present disclosure pertains to a polishing liquid composition for a silicon substrate, the polishing liquid composition containing the following component A and the following component B and having a pH of 8.5-14 (exclusive of 8.5). The component A is silica particles. The component B is an amino group-containing water‐soluble polymer having a pKa of 5-8.5.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a polishing composition for silicon substrates, a polishing method using the same, and a method for producing a semiconductor substrate. [Background technology]

[0002] Polishing compositions containing silica particles are known as polishing compositions used for polishing silicon substrates used in the manufacture of semiconductor substrates. In this type of polishing composition, problems arise such as the occurrence of surface defects (LPD: Light Point Defects) on silicon substrates caused by the aggregation of silica particles, and filter clogging when filtering the polishing composition to remove the aggregates (see, for example, JP 2008-53415 A). In addition, polishing compositions containing water-soluble polymer compounds are known for the purpose of improving the polishing rate (see JP 2007-19093 A and JP 11-116942 A).

[0003] In order to reduce LPD, Japanese Patent Application Laid-Open No. 2008-53415 proposes a polishing composition containing an alkali and at least one water-soluble polymer selected from polyvinylpyrrolidone and poly-N-vinylformamide. Japanese Patent Application Laid-Open No. 2007-19093 proposes a polishing composition containing a water-soluble polymer compound that contains a nitrogen-containing group, such as polyethyleneimine. Japanese Patent Application Laid-Open No. 11-116942 proposes a polishing composition containing hydroxyethyl cellulose (HEC) in order to improve the polishing rate and the wettability of the surface of an object to be polished. Summary of the Invention

[0004] In one aspect, the present disclosure relates to a polishing liquid composition for silicon substrates, comprising the following component A and component B, and having a pH of more than 8.5 and not more than 14: Component A: Silica particles Component B: an amino group-containing water-soluble polymer having a pKa of 5 or more and 8.5 or less

[0005] In one aspect, the present disclosure relates to a method for polishing a silicon substrate, comprising a step of polishing a silicon substrate to be polished with the polishing liquid composition of the present disclosure.

[0006] In one aspect, the present disclosure relates to a method for producing a semiconductor substrate, the method including: polishing a silicon substrate to be polished with the polishing liquid composition of the present disclosure; and cleaning the polished silicon substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] However, in polishing using the polishing composition of JP-A-2008-53415, the removal rate is not sufficient. When the polishing composition of JP 2007-19093 A is used, there is a problem that silica particles aggregate due to the water-soluble polymer compound containing a nitrogen-containing group, resulting in deterioration of the surface condition of the silicon substrate, such as the generation of scratches. When the polishing composition containing HEC described in JP-A-11-116942 is used, agglomerations of silica particles are likely to occur, and even if the polishing composition is filtered, the filter immediately becomes clogged, which is a problem in that the polishing composition cannot be filtered immediately before polishing. Furthermore, polishing compositions are usually stored and transported in the form of concentrates, and therefore storage stability in the form of concentrates is also required.

[0008] The present disclosure provides a polishing composition for silicon substrates, which can achieve both an improved removal rate and storage stability of a concentrate, and a method for polishing a silicon substrate and a method for manufacturing a semiconductor substrate using the same.

[0009] The present disclosure is based on the finding that by using a polishing liquid composition for silicon substrates that contains silica particles and an amino group-containing water-soluble polymer having a pKa of 5 or more and 8.5 or less, and has a pH of more than 8.5 and 14 or less, silicon substrates can be polished at high speed and the concentrate has excellent storage stability.

[0010] That is, in one aspect, the present disclosure relates to a polishing liquid composition for silicon substrates (hereinafter also referred to as the "polishing liquid composition of the present disclosure") that contains the following component A and the following component B and has a pH of more than 8.5 and 14 or less. Component A: Silica particles Component B: an amino group-containing water-soluble polymer having a pKa of 5 or more and 8.5 or less

[0011] According to the present disclosure, in one or a plurality of embodiments, it is possible to provide a polishing liquid composition for silicon substrates that can achieve both an improvement in removal rate and storage stability of the concentrate.

[0012] Although the details of the mechanism by which the effects of the present disclosure are exerted are not clear, it is presumed as follows. Under alkaline polishing conditions with a pH greater than 8.5 and equal to or less than 14, both the silica abrasive grains and the silicon substrate to be polished have negative charges, and electrostatic repulsion is always generated. In order to improve the polishing rate, it is effective to alleviate this electrostatic repulsion, and the negative charges on both surfaces can be alleviated by using a cationic substance, but doing so causes aggregation between the silica particles, resulting in a new problem of reduced storage stability of the polishing composition, particularly the storage stability of a concentrate of the polishing composition. Therefore, when focusing on water-soluble polymers having amino groups, it is considered that the amino group-containing water-soluble polymer (component B) having a pKa smaller than the pH of the polishing compound composition has low cationicity and is adsorbed to the silica particles (component A) and the silicon substrate to be polished mainly by the van der Waals force of the whole molecule rather than by electrostatic interaction with the amino groups. Therefore, it is considered that the electrostatic repulsion between the silica particles (component A) and the silicon substrate to be polished is moderately alleviated, the aggregation of the silica particles is suppressed, and both the improvement of the polishing rate and the storage stability can be achieved. However, the present disclosure need not be construed as being limited to these mechanisms.

[0013] [Polished silicon substrate] The polishing liquid composition of the present disclosure is a polishing composition for silicon substrates, and can be used, for example, in a polishing step of polishing a silicon substrate to be polished in a method for manufacturing a semiconductor substrate, or in a polishing step of polishing a silicon substrate to be polished in a method for polishing a silicon substrate. In one or more embodiments, the silicon substrate to be polished using the polishing liquid composition of the present disclosure can be a silicon substrate, etc., and in one or more embodiments, a single crystal silicon substrate, a polysilicon substrate, a substrate having a polysilicon film, a SiN substrate, etc. can be used. From the viewpoint of exerting the effect of the polishing liquid composition of the present disclosure, a single crystal silicon substrate or a polysilicon substrate is preferred, and a single crystal silicon substrate is more preferred.

[0014] [Silica particles (component A)] The polishing liquid composition of the present disclosure contains silica particles (hereinafter also referred to as "Component A") as an abrasive. Component A includes colloidal silica, fumed silica, pulverized silica, and surface-modified silica thereof, and from the viewpoint of achieving both improved polishing rate and storage stability, and from the viewpoint of improving surface quality such as reducing surface roughness (haze), surface defects, and scratches, colloidal silica is preferred. Component A may be one type or a combination of two or more types.

[0015] From the viewpoint of operability, the use form of component A is preferably a slurry form.When component A contained in the polishing liquid composition of the present disclosure is colloidal silica, from the viewpoint of preventing contamination of silicon substrate by alkali metal, alkaline earth metal, etc., the colloidal silica is preferably obtained from the hydrolysis product of alkoxysilane.The silica particles obtained from the hydrolysis product of alkoxysilane can be produced by a conventionally known method.

[0016] From the viewpoint of maintaining the polishing rate, the average primary particle diameter of component A is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 30 nm or more, and from the viewpoint of improving storage stability and improving surface quality such as reducing surface roughness (haze), surface defects, and scratches, the average primary particle diameter of component A is preferably 50 nm or less, more preferably 45 nm or less, and even more preferably 40 nm or less. From the same viewpoint, the average primary particle diameter of component A is preferably 10 nm or more and 50 nm or less, more preferably 20 nm or more and 45 nm or less, and even more preferably 30 nm or more and 40 nm or less. In the present disclosure, the average primary particle size of component A is determined by the specific surface area S (m 2 The average primary particle size is calculated using the formula (1 / g). The average primary particle size is a value measured by the method described in the Examples.

[0017] From the viewpoint of maintaining the polishing rate, the average secondary particle diameter of component A is preferably 20 nm or more, more preferably 30 nm or more, even more preferably 40 nm or more, and even more preferably 60 nm or more, and from the viewpoint of improving storage stability and improving surface quality such as reducing surface roughness (haze), surface defects, and scratches, the average secondary particle diameter of component A is preferably 100 nm or less, more preferably 90 nm or less, and even more preferably 80 nm or less. From the same viewpoint, the average secondary particle diameter of component A is preferably 20 nm or more and 100 nm or less, more preferably 40 nm or more and 90 nm or less, and even more preferably 60 nm or more and 80 nm or less. In the present disclosure, the average secondary particle size is a value measured by a dynamic light scattering (DLS) method, and is a value measured by the method described in the Examples.

[0018] From the viewpoints of improving the storage stability and improving the surface quality, the degree of association of component A is preferably 3 or less, more preferably 2.5 or less, and even more preferably 2.3 or less, and from the viewpoints of achieving both an improvement in the removal rate and storage stability, and of improving the surface quality, the degree of association of component A is preferably 1.1 or more, more preferably 1.5 or more, and even more preferably 1.8 or more.

[0019] In the present disclosure, the degree of association of component A is a coefficient representing the shape of the silica particles and is calculated by the following formula. Degree of association = average secondary particle size / average primary particle size

[0020] The degree of association of Component A can be adjusted by using the methods described in, for example, JP-A-6-254383, JP-A-11-214338, JP-A-11-60232, JP-A-2005-060217, JP-A-2005-060219, and the like.

[0021] The shape of component A is preferably a so-called spherical shape and / or a so-called cocoon shape from the viewpoints of achieving both an improvement in removal rate and storage stability, and from the viewpoints of improving surface quality.

[0022] The content of Component A in the polishing composition of the present disclosure is, from the viewpoint of improving the polishing rate, SiO 2 In terms of conversion, the content is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, even more preferably 0.07 mass% or more, and from the viewpoint of improving storage stability and surface quality, it is preferably 2.5 mass% or less, more preferably 1 mass% or less, and even more preferably 0.8 mass% or less. Therefore, the content of component A in the polishing liquid composition of the present disclosure is preferably 0.01 mass% or more and 2.5 mass% or less, more preferably 0.05 mass% or more and 1 mass% or less, and even more preferably 0.07 mass% or more and 0.8 mass% or less. When component A is a combination of two or more types, the content of component A refers to the total content thereof. Furthermore, when the silicon substrate to be polished is a single crystal silicon substrate, the content of component A in the polishing liquid composition of the present disclosure is more preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and even more preferably 0.2% by mass or less, from the viewpoint of improving storage stability and surface quality. Therefore, the content of component A in the polishing liquid composition of the present disclosure is more preferably 0.07% by mass or more and 0.5% by mass or less, more preferably 0.07% by mass or more and 0.3% by mass or less, and even more preferably 0.07% by mass or more and 0.2% by mass or less. Furthermore, when the silicon substrate to be polished is a polysilicon substrate, the content of component A in the polishing liquid composition of the present disclosure is more preferably 0.1 mass% or more, more preferably 0.2 mass% or more, and even more preferably 0.3 mass% or more, from the viewpoint of improving the polishing rate. Therefore, the content of component A in the polishing liquid composition of the present disclosure is more preferably 0.1 mass% or more and 0.8 mass% or less, even more preferably 0.2 mass% or more and 0.8 mass% or less, and even more preferably 0.3 mass% or more and 0.8 mass% or less.

[0023] [Amino group-containing water-soluble polymer (component B) having a pKa of 5 or more and 8.5 or less] The polishing liquid composition of the present disclosure contains an amino group-containing water-soluble polymer (hereinafter also referred to as "component B") having a pKa of 5 or more and 8.5 or less. It is believed that component B can adjust the zeta potential of the silica particles (component A) and the silicon substrate to be polished, and suppress the aggregation of the silica particles while reducing the electrostatic repulsion between the silica particles (component A) and the silicon substrate to be polished. In the present disclosure, "water-soluble" means having a solubility of 0.5 g / 100 mL or more in water (20°C), preferably a solubility of 2 g / 100 mL or more.

[0024] The pKa of component B is, from the viewpoint of improving the removal rate, 5 or more, preferably 5.5 or more, more preferably 5.9 or more, and even more preferably 6.3 or more, and from the viewpoint of improving the surface quality, it is, from 8.5 or less, preferably 8.3 or less, more preferably 8.1 or less, and even more preferably 8 or less. Furthermore, when component B is component B1 described later, the pKa of component B is more preferably 6.5 or more from the viewpoint of improving the polishing rate, and more preferably 7.7 or less, more preferably 7.4 or less, and still more preferably 7.1 or less, from the viewpoint of improving the surface quality. Furthermore, when component B is component B2 described later, from the viewpoint of improving the polishing rate, the pKa of component B is more preferably 6.6 or more, more preferably 6.9 or more, and more preferably 7.1 or more, and from the viewpoint of improving the surface quality, it is more preferably 7.8 or less, more preferably 7.6 or less, and more preferably 7.4 or less.

[0025] From the viewpoint of achieving both an improvement in the polishing rate and storage stability, it is preferable that Component B contains one or more monomer-derived structural units selected from allylamine and diallylamine. From the viewpoint of availability, in one or more embodiments, Component B is preferably an amino group-containing water-soluble polymer containing a structural unit derived from allylamine (hereinafter also referred to as "Component B1"), and in one or more embodiments, it is preferably an amino group-containing water-soluble polymer containing a structural unit derived from diallylamine (hereinafter also referred to as "Component B2").

[0026] (Component B1: Amino group-containing water-soluble polymer containing structural units derived from allylamine) In one or more embodiments, at least a part of the amino groups in the allylamine-derived structural unit preferably has a steric shielding group from the viewpoint of improving the polishing rate and maintaining storage stability, and from the viewpoint of availability. In the present disclosure, the steric shielding group refers to a three-dimensional (bulky) substituent that can shield the nitrogen atom of the amino group of component B to suppress cationization, i.e., lower the pKa. From the same viewpoint, the amino group having a steric shielding group is preferably a secondary amino group or a tertiary amino group containing a hydrocarbon group having 3 to 11 carbon atoms and having a hydroxyl group. The number of carbon atoms in the hydrocarbon group is preferably 3 or more from the viewpoint of improving the shielding property of the amino group (suppressing the cationization of the nitrogen atom of the amino group) and from the viewpoint of improving the polishing rate and maintaining storage stability, and is preferably 11 or less, more preferably 7 or less, even more preferably 5 or less, and even more preferably 4 or less, from the viewpoint of improving water solubility and availability.

[0027] In one or more embodiments, the amino group having a sterically shielding group is a modified group of an amino group by a glycidol derivative, and in one or more embodiments, is a group formed by reacting an amino group in a structural unit derived from allylamine with a glycidol derivative. At least a part of the amino groups among all the amino groups of component B1 is modified by the glycidol derivative to become an amino group having a sterically shielding group. The equivalent of the glycidol derivative relative to the number of amino groups (1 equivalent) in the structural unit derived from allylamine (hereinafter also referred to as the "glycidol modification rate") is, from the viewpoint of improving the storage stability and from the viewpoint of improving the surface quality, preferably 0.3 or more, more preferably 0.5 or more, even more preferably 0.8 or more, even more preferably 1 or more, preferably more than 1.1, more preferably 1.2 or more, even more preferably 1.3 or more, even more preferably 1.4 or more, and even more preferably 1.5 or more, and from the viewpoint of improving the polishing rate, it is preferably 4 or less, more preferably 3 or less, even more preferably 2.5 or less, even more preferably 2 or less, even more preferably 1.9 or less, and even more preferably 1.6 or less.

[0028] In the present disclosure, the glycidol modification rate is 13 The glycidol modification rate is a value measured by the method described in the Examples using C-NMR, however, the glycidol modification rate can also be measured by the following method (1) or (2). (1) It can be calculated from the amino group equivalent of the allylamine polymer and the number of moles of the glycidol derivative used as the reaction raw material. (2) The nitrogen content N (mass%) of the reaction product of a glycidol derivative and an allylamine polymer is measured, and the nitrogen content N can be calculated from the following formula. Glycidol modification rate = A / B Here, A=(100-N×molecular weight of allylamine monomer / 14) / molecular weight of glycidol derivative, and B=N / 14.

[0029] Examples of the glycidol derivative include glycidol and alkyl glycidyl ether, and glycidol is preferred from the viewpoint of availability and from the viewpoint of achieving both improved polishing rate and storage stability. The alkyl group of the alkyl glycidyl ether is preferably an alkyl group having 1 to 8 carbon atoms from the viewpoint of availability, and examples of the alkyl group include methyl, ethyl, propyl, butyl, and 2-ethylhexyl. Specific examples of the alkyl glycidyl ether include methyl glycidyl ether and 2-ethylhexyl glycidyl ether.

[0030] In one or more embodiments, component B1 may be a polyallylamine in which at least a portion of amino groups has a sterically shielding group, and in one or more embodiments, may be a reaction product of a polyallylamine with a glycidol derivative.

[0031] In one or more embodiments, an example of Component B1 is a compound containing a structural unit represented by the following formula (I) (glycidol-modified polyallylamine). [ka]

[0032] In formula (I), R 1 and R 2 are each a hydrogen atom or a sterically shielding group. Examples of the sterically shielding group include a modification group derived from a glycidol derivative, and in one or more embodiments, a 1-mol adduct or 2-mol adduct of glycidol is included. In one or more embodiments, -CH 2 CH(OH)CH 2 (OH), -CH 2 CH(OH)CH 2 O-CH 2 CH(OH)CH 2 (OH) and the like.

[0033] (Component B2: Amino group-containing water-soluble polymer containing a constitutional unit derived from diallylamine) In one or more embodiments, from the viewpoint of achieving both an improvement in the polishing rate and storage stability, at least a part of the amino groups in the diallylamine-derived constitutional unit preferably has an electron-withdrawing group at the β-position or γ-position of the amino group. Examples of the electron-withdrawing group include a group represented by the following formula (II).

[0034] [ka]

[0035] In one or more embodiments, component B2 includes a compound containing a diallylamine-derived constituent unit and a sulfur dioxide-derived constituent unit, for example, a compound containing a constituent unit represented by the following formula (III). [ka]

[0036] In formula (III), R 3 is an alkyl group having 1 to 3 carbon atoms which may have a hydroxyl group. From the viewpoint of availability and economic efficiency, R 3 is preferably a methyl group. Also, n+m=1, and n and m are 0 or 1. From the same viewpoint, a compound where m=1 and n=0 is preferred. A mixture of a compound where m=1 and n=0 and a compound where m=0 and n=1 may also be used.

[0037] In one or more embodiments, Component B2 includes a compound containing a constituent unit represented by the following formula (IV), such as a methyldiallylamine / sulfur dioxide copolymer. [ka]

[0038] From the viewpoint of improving the polishing rate, the weight average molecular weight of component B is preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, and even more preferably 2,000 or more, and from the viewpoint of achieving both an improvement in the polishing rate and storage stability and reducing surface roughness and surface defects, it is preferably 100,000 or less, more preferably 50,000 or less, even more preferably 30,000 or less, even more preferably 20,000 or less, even more preferably 15,000 or less, and even more preferably 12,000 or less. The weight average molecular weight of component B in the present disclosure can be measured, for example, by the method described in the Examples.

[0039] When Component B is Component B1, from the viewpoint of improving the polishing rate, the weight average molecular weight of Component B is preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, even more preferably 2,000 or more, preferably 3,000 or more, more preferably 5,000 or more, even more preferably 6,000 or more, and even more preferably 7,000 or more; and from the viewpoint of achieving both an improvement in the polishing rate and storage stability and of reducing surface roughness and surface defects, it is preferably 100,000 or less, more preferably 50,000 or less, even more preferably 30,000 or less, even more preferably 20,000 or less, even more preferably 15,000 or less, even more preferably 12,000 or less, and even more preferably 10,000 or less.

[0040] When Component B is Component B2, from the viewpoint of improving the polishing rate, the weight average molecular weight of Component B is preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, and even more preferably 2,000 or more. From the viewpoint of achieving both an improvement in the polishing rate and storage stability, and from the viewpoint of reducing surface roughness and surface defects, it is preferably 100,000 or less, more preferably 50,000 or less, even more preferably 30,000 or less, even more preferably 20,000 or less, even more preferably 15,000 or less, even more preferably 12,000 or less, even more preferably 10,000 or less, even more preferably 7,000 or less, even more preferably 5,000 or less, and even more preferably 4,000 or less.

[0041] The content of component B in the polishing composition of the present disclosure is preferably 10 ppm by mass or more, more preferably 20 ppm by mass or more, and even more preferably 30 ppm by mass or more, from the viewpoint of achieving both an improvement in the polishing rate and storage stability, and from the same viewpoint, is preferably 200 ppm by mass or less, more preferably 150 ppm by mass or less, and even more preferably 120 ppm by mass or less. In the present disclosure, 1% by mass is 10,000 ppm by mass (the same applies below).

[0042] The ratio of the content of component B to the content of component A in the polishing liquid composition of the present disclosure (mass ratio B / A) is preferably 0.008 or more, more preferably 0.016 or more, and even more preferably 0.025 or more from the viewpoint of improving storage stability, and is preferably 0.16 or less, more preferably 0.12 or less, and even more preferably 0.09 or less from the viewpoint of improving the polishing rate.

[0043] [water] In one or more embodiments, the polishing liquid composition of the present disclosure may contain water. Examples of water include ion-exchanged water and ultrapure water. The content of water in the polishing liquid composition of the present disclosure may be, for example, the remainder of component A, component B, and any optional components described below.

[0044] [Nitrogen-containing basic compound (component C)] In one or more embodiments, the polishing liquid composition of the present disclosure preferably further contains a nitrogen-containing basic compound (hereinafter also referred to as "component C") from the viewpoint of adjusting the pH. Component C is preferably a water-soluble nitrogen-containing basic compound from the viewpoint of achieving both improved polishing rate and storage stability, and from the viewpoint of improving surface quality. In the present disclosure, "water-soluble" refers to having a solubility of 0.5 g / 100 mL or more, preferably 2 g / 100 mL or more, in water (20°C). In the present disclosure, "water-soluble nitrogen-containing basic" refers to a nitrogen-containing compound that exhibits basicity when dissolved in water. In one or more embodiments, component C does not include an amino group-containing water-soluble polymer (component B). Component C may be one type or a combination of two or more types.

[0045] In one or more embodiments, component C may be at least one selected from an amine compound and an ammonium compound. For example, component C may be one or a combination of two or more selected from ammonia, ammonium hydroxide, ammonium carbonate, ammonium hydrogen carbonate, dimethylamine, trimethylamine, diethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, N-methylethanolamine, N-methyl-N,N-diethanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, N,N-dibutylethanolamine, N-(β-aminoethyl)ethanolamine, monoisopropanolamine, diisopropanolamine, triisopropanolamine, ethylenediamine, hexamethylenediamine, piperazine hexahydrate, anhydrous piperazine, 1-(2-aminoethyl)piperazine, N-methylpiperazine, diethylenetriamine, tetramethylammonium hydroxide, and hydroxylamine. Among these, from the viewpoint of achieving both an improvement in the removal rate and storage stability, Component C is preferably ammonia or a mixture of ammonia and hydroxyamine, and more preferably ammonia.

[0046] When the polishing liquid composition of the present disclosure contains component C, the content of component C in the polishing liquid composition of the present disclosure is preferably 5 mass ppm or more, more preferably 10 mass ppm or more, and even more preferably 20 mass ppm or more from the viewpoint of improving the polishing rate, and is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, more preferably 150 mass ppm or less, and even more preferably 100 mass ppm or less from the viewpoint of improving storage stability, improving surface quality, and suppressing corrosion of the silicon substrate. From the same viewpoint, the content of component C in the polishing liquid composition of the present disclosure is preferably 5 mass ppm or more and 500 mass ppm or less, more preferably 10 mass ppm or more and 300 mass ppm or less, more preferably 20 mass ppm or more and 150 mass ppm or less, and even more preferably 20 mass ppm or more and 100 mass ppm or less. When component C is a combination of two or more kinds, the content of component C refers to the total content thereof.

[0047] When the polishing liquid composition of the present disclosure contains component C, the ratio C / A (mass ratio C / A) of the content of component C to the content of component A in the polishing liquid composition of the present disclosure is preferably 0.002 or more, more preferably 0.01 or more, even more preferably 0.015 or more, and even more preferably 0.025 or more from the viewpoint of improving the polishing rate, and from the viewpoint of improving storage stability, improving surface quality, and suppressing corrosion of the silicon substrate, it is preferably 1 or less, more preferably 0.5 or less, even more preferably 0.1 or less, and even more preferably 0.08 or less. From the same viewpoint, the mass ratio C / A in the polishing liquid composition of the present disclosure is preferably 0.002 or more and 1 or less, more preferably 0.01 or more and 0.5 or less, even more preferably 0.015 or more and 0.1 or less, and even more preferably 0.025 or more and 0.08 or less.

[0048] [Other ingredients] The polishing liquid composition of the present disclosure may further contain other components to the extent that the effects of the present disclosure are not impaired. In one or more embodiments, the other components include a water-soluble polymer other than Component B, a pH adjuster other than Component C, a preservative, an alcohol, a chelating agent, an oxidizing agent, and the like.

[0049] [pH] The pH of the polishing liquid composition of the present disclosure is more than 8.5, preferably 9 or more, more preferably 9.5 or more, and more preferably 10 or more, from the viewpoint of improving the polishing rate and storage stability, and is 14 or less, preferably 13 or less, more preferably 12.5 or less, more preferably 12 or less, more preferably 11.5 or less, and more preferably 11 or less, from the viewpoint of improving the surface quality. From the same viewpoint, the pH of the polishing liquid composition of the present disclosure is more than 8.5 to 14 or less, more preferably 9 to 13 or less, more preferably 9 to 12.5 or less, more preferably 9 to 12 or less, more preferably 9.5 to 11.5 or less, and more preferably 10 to 11 or less. The pH of the polishing liquid composition of the present disclosure can be adjusted using component C or a known pH adjuster. In the present disclosure, the above pH is a value measured by the method described in the Examples.

[0050] [pH-pKa] From the viewpoint of achieving both an improvement in the polishing rate and storage stability, and from the viewpoint of improving surface quality, the pH of the polishing liquid composition of the present disclosure is preferably higher than the pKa of component B. Specifically, from the viewpoint of achieving both an improvement in the polishing rate and storage stability, the difference between the pH and the pKa (pH-pKa) is preferably more than 0, more preferably 0.5 or more, even more preferably 1 or more, even more preferably 1.5 or more, even more preferably 2 or more, and even more preferably 2.5 or more, and from the viewpoint of improving surface quality, it is preferably 7 or less, more preferably 6 or less, even more preferably 5.5 or less, even more preferably 5 or less, even more preferably 4.5 or less, even more preferably 4 or less, and even more preferably 3.5 or less.

[0051] The polishing liquid composition of the present disclosure can be produced, for example, by blending component A and component B, and, if desired, water, component C, and other components by a known method. That is, the polishing liquid composition of the present disclosure can be produced, for example, by blending at least component A and component B. Therefore, in another aspect, the present disclosure relates to a method for producing a polishing liquid composition, which includes a step of blending at least component A and component B. In the present disclosure, "blending" includes mixing component A, component B, and, if necessary, water, component C, and other components simultaneously or in any order. The blending can be performed using, for example, a stirrer such as a homomixer, a homogenizer, an ultrasonic disperser, a wet ball mill, or a bead mill. The preferred blending amount of each component in the method for producing a polishing liquid composition of the present disclosure can be the same as the preferred content of each component in the polishing liquid composition of the present disclosure described above.

[0052] In the present disclosure, "the content of each component in the polishing liquid composition" refers to the content of each component at the time of use, that is, at the time when the polishing liquid composition is started to be used for polishing.

[0053] The polishing liquid composition of the present disclosure may be produced as a concentrate from the viewpoint of storage and transportation, and diluted at the time of use. The dilution ratio is preferably 2 times or more, more preferably 10 times or more, even more preferably 30 times or more, even more preferably 50 times or more from the viewpoint of production and transportation costs and storage stability, and is preferably 180 times or less, more preferably 140 times or less, even more preferably 100 times or less, even more preferably 70 times or less from the viewpoint of storage stability. The polishing liquid composition concentrate of the present disclosure can be used by diluting with water so that the content of each component at the time of use is the above-mentioned content (i.e., the content at the time of use). In the present disclosure, the "time of use" of the polishing liquid composition concentrate refers to the state in which the polishing liquid composition concentrate is diluted.

[0054] [Polishing liquid kit] In another aspect, the present disclosure relates to a polishing liquid kit for producing the polishing liquid composition of the present disclosure (hereinafter, also referred to as the "kit of the present disclosure"). According to the kit of the present disclosure, a polishing liquid composition that can achieve both an improvement in the polishing rate and storage stability of the concentrate can be obtained. In one or more embodiments, the kit of the present disclosure may be a polishing liquid kit containing a solution containing component A, component B, and component C. The solution may contain other components as required. The solution may be diluted with water as required at the time of use.

[0055] [Silicon substrate polishing method] In another aspect, the present disclosure relates to a method for polishing a silicon substrate (hereinafter also referred to as the "polishing method of the present disclosure"), which includes a step of polishing a silicon substrate to be polished using the polishing composition of the present disclosure (hereinafter also referred to as the "polishing step"). According to the polishing method of the present disclosure, since the polishing composition of the present disclosure is used, both an improvement in the polishing rate and an improvement in the surface quality can be achieved.

[0056] In the polishing step of the polishing method of the present disclosure, for example, the silicon substrate can be pressed against a platen to which a polishing pad is attached, and the silicon substrate can be polished at a polishing pressure of 3 to 20 kPa. In the present disclosure, the polishing pressure refers to the pressure of the platen applied to the surface of the silicon substrate during polishing.

[0057] In the polishing step of the polishing method of the present disclosure, for example, a silicon substrate to be polished can be pressed against a platen to which a polishing pad is attached, and the silicon substrate to be polished can be polished with a polishing liquid composition and a polishing pad surface temperature of 15° C. to 40° C. From the viewpoint of achieving both an improvement in the polishing rate and surface quality such as a reduction in surface roughness (haze), the temperature of the polishing liquid composition and the polishing pad surface temperature are preferably 15° C. or higher or 20° C. or higher, and preferably 40° C. or lower or 30° C. or lower.

[0058] [Method of manufacturing semiconductor substrate] In another aspect, the present disclosure relates to a method for producing a semiconductor substrate (hereinafter also referred to as the "semiconductor substrate production method of the present disclosure"), which includes a step of polishing a silicon substrate to be polished using the polishing liquid composition of the present disclosure (hereinafter also referred to as the "polishing step") and a step of cleaning the polished silicon substrate (hereinafter also referred to as the "cleaning step"). According to the semiconductor substrate production method of the present disclosure, by using the polishing liquid composition of the present disclosure, it is possible to achieve both an improvement in the polishing rate and storage stability of the concentrate, so that a high-quality semiconductor substrate can be produced at a high yield, high productivity, and low cost.

[0059] The polishing step in the semiconductor substrate manufacturing method of the present disclosure can include, for example, a lapping (rough polishing) step of planarizing a single crystal silicon substrate obtained by slicing a single crystal silicon ingot into a thin disk shape, and a finish polishing step of mirror-finishing the surface of the single crystal silicon substrate after etching the lapped single crystal silicon substrate. The polishing liquid composition of the present disclosure is more preferably used in the finish polishing step from the viewpoint of achieving both an improvement in the polishing rate and an improvement in the surface quality.

[0060] The polishing step in the semiconductor substrate manufacturing method of the present disclosure can include, for example, a step of removing irregularities in the polysilicon film to planarize a substrate in which a polysilicon film is formed by chemical vapor deposition (CVD) on a silicon substrate having a silicon dioxide film and a silicon nitride film, and a step of simultaneously polishing and planarizing the silicon dioxide film and silicon nitride film directly below and the polysilicon film. From the viewpoint of achieving both an improvement in the polishing rate and an improvement in the surface quality, the polishing liquid composition of the present disclosure is more preferably used in the step of removing irregularities in the polysilicon film to planarize the substrate.

[0061] The polishing step in the semiconductor substrate manufacturing method of the present disclosure can be performed under the same conditions (polishing pressure, polishing liquid composition, surface temperature of polishing pad, etc.) as those in the polishing step in the polishing method of the present disclosure described above.

[0062] In one or more embodiments, the method for producing a semiconductor substrate according to the present disclosure may include a dilution step of diluting a concentrate of the polishing liquid composition according to the present disclosure prior to the polishing step. The dilution medium may be, for example, water.

[0063] In the cleaning step in the semiconductor substrate manufacturing method of the present disclosure, it is preferable to perform inorganic cleaning from the viewpoint of reducing residues on the silicon substrate surface. Examples of the cleaning agent used in inorganic cleaning include inorganic cleaning agents containing at least one selected from hydrogen peroxide, ammonia, hydrochloric acid, sulfuric acid, hydrofluoric acid, and ozone water.

[0064] In one or a plurality of embodiments, the semiconductor substrate manufacturing method of the present disclosure can further include, after the cleaning step, a step of rinsing the cleaned silicon substrate with water and drying it.

[0065] The present disclosure further relates to one or more of the following embodiments. <1> A polishing liquid composition for silicon substrates, comprising the following component A and component B, and having a pH of more than 8.5, preferably 9 or more, more preferably 9.5 or more, even more preferably 10 or more, and 14 or less, preferably 13 or less, more preferably 12.5 or less, more preferably 12 or less, even more preferably 11.5 or less, even more preferably 11 or less. Component A: Silica particles Component B: an amino group-containing water-soluble polymer having a pKa of 5 or more, preferably 5.5 or more, more preferably 5.9 or more, more preferably 6.3 or more, and 8.5 or less, preferably 8.3 or less, more preferably 8.1 or less, more preferably 8 or less. <2> The difference between pH and pKa (pH-pKa) is greater than 0, preferably 0.5 or more, more preferably 1 or more, even more preferably 1.5 or more, even more preferably 2 or more, even more preferably 2.5 or more, and is 7 or less, preferably 6 or less, more preferably 5.5 or less, even more preferably 5 or less, even more preferably 4.5 or less, even more preferably 4 or less, even more preferably 3.5 or less; <1> The polishing composition according to claim 1 . <3> Component B contains one or more monomers selected from allylamine and diallylamine, preferably a constitutional unit derived from diallylamine; <1> or <2> The polishing composition according to claim 1 . <4> At least a part of the amino groups in the constitutional unit derived from allylamine has a sterically shielding group. <3> The polishing composition according to claim 1 . <5> At least a part of the amino groups in the structural unit derived from allylamine is a secondary amino group or a tertiary amino group containing a hydrocarbon group having 3 to 11 carbon atoms and a hydroxyl group. <3> or <4> The polishing composition according to claim 1 . <6> Component B is a reaction product of polyallylamine with a glycidol derivative, preferably a glycidol-modified polyallylamine; <1> from <5> 2. The polishing composition according to claim 1 , <7> At least a part of the amino groups in the constitutional unit derived from diallylamine has an electron-withdrawing group, preferably a group represented by the following formula (II), at the β-position or γ-position: <3> The polishing composition according to claim 1 . [ka] <8> Component B is a compound containing a structural unit represented by the following formula (III): <1> from <7> 2. The polishing composition according to claim 1 , [ka] In formula (III), R 3 is an alkyl group having 1 to 3 carbon atoms which may have a hydroxyl group, preferably a methyl group, and n+m=1, preferably m=1 and n=0. <9> In the polishing liquid composition of the present disclosure, the ratio of the content of component B to the content of component A (mass ratio B / A) is 0.008 or more, preferably 0.016 or more, more preferably 0.025 or more, and is 0.16 or less, preferably 0.12 or less, more preferably 0.09 or less. <1> from <8> 2. The polishing composition according to claim 1 , <10> The polishing composition of the present disclosure contains a nitrogen-containing basic compound (component C), preferably a water-soluble nitrogen-containing basic compound, more preferably at least one selected from an amine compound and an ammonium compound, and further preferably ammonia. <1> from <9> 2. The polishing composition according to claim 1 , <11> When the polishing liquid composition of the present disclosure contains component C, the ratio C / A of the content of component C to the content of component A in the polishing liquid composition of the present disclosure (mass ratio C / A) is 0.002 or more, preferably 0.01 or more, more preferably 0.015 or more, even more preferably 0.025 or more, and is 1 or less, preferably 0.5 or less, more preferably 0.1 or less, even more preferably 0.08 or less. <10> The polishing composition according to claim 1 . <12> <1> from <11> 2. A method for polishing a silicon substrate, comprising the step of polishing a silicon substrate to be polished with the polishing composition according to claim 1. <13> The silicon substrate to be polished is a single crystal silicon substrate or a polysilicon substrate, preferably a single crystal silicon substrate; <12> The polishing method according to claim 1. <14> <1> from <11> polishing a silicon substrate to be polished using the polishing composition according to any one of the preceding claims; and cleaning the polished silicon substrate. EXAMPLES

[0066] The present disclosure will be described in more detail below with reference to examples, but these are merely illustrative and the present disclosure is not limited to these examples.

[0067] 1. Preparation of polishing composition (Polishing composition concentrate) A concentrate (60 times) of the polishing liquid composition was obtained by mixing and stirring the silica particles (component A) shown in Tables 1 and 2, the water-soluble polymer (component B or non-component B) shown in Tables 1 and 2, ammonia (component C), and ultrapure water. The pH of the concentrate at 25°C was 10.6 to 11.0. (polishing liquid composition) The concentrate was diluted 60 times with ion-exchanged water to obtain polishing liquid compositions of Examples 1 to 9 and Comparative Examples 1 to 3. The content of each component in Tables 1 and 2 is the content of each component (mass % or mass ppm, active content) at the time of use of the diluted polishing liquid composition. The content of ultrapure water is the remainder excluding component A and component B or non-component B and component C. The pH of each polishing liquid composition (at the time of use) at 25°C was 10.3. The pH at 25° C. was measured using a pH meter (Toa Denpa Kogyo Co., Ltd., HM-30G), and was the value measured one minute after immersing the electrodes of the pH meter in the polishing composition or a concentrate thereof.

[0068] The following components A, B, non-component B, and C were used in the preparation of each polishing composition. (Component A) Colloidal silica [average primary particle size 35 nm, average secondary particle size 70 nm, degree of association 2.0] (Component B) B1: Methyldiallylamine-sulfur dioxide copolymer [Nittobo Medical Co., Ltd., PAS-2201, weight average molecular weight 3,000] B2: Glycidol-modified polyallylamine (glycidol modification rate: 2.0) [manufactured by Nittobo Medical Co., Ltd., weight average molecular weight 11,000] B3: Glycidol-modified polyallylamine (glycidol modification rate: 1.8) [manufactured by Nittobo Medical Co., Ltd., weight average molecular weight 10,200] B4: Glycidol-modified polyallylamine (glycidol modification rate: 1.5) [manufactured by Nittobo Medical Co., Ltd., weight average molecular weight 8,900] B5: Glycidol-modified polyallylamine (glycidol modification rate: 1.0) [manufactured by Nittobo Medical Co., Ltd., weight average molecular weight 6,900] (Non-ingredient B) B6: Allylamine (free) polymer [Nittobo Medical PAA-03, weight average molecular weight 3,000] B7: Polyethyleneimine [Nippon Shokubai, SP-200, weight average molecular weight 10,000] (Component C) Ammonia [28% by weight ammonia water, Kishida Chemical Co., Ltd., special grade reagent]

[0069] 2.Measuring methods for various parameters (1) Measurement of the average primary particle size of silica particles (component A) The average primary particle size (nm) of component A is calculated by the BET (nitrogen adsorption) method. 2 / g) using the following formula: Average primary particle diameter (nm)=2727 / S

[0070] The specific surface area S of component A was measured by carrying out the following [pretreatment], and then weighing out approximately 0.1 g of the measurement sample into a measurement cell to four decimal places, drying the sample for 30 minutes in an atmosphere at 110°C immediately before measuring the specific surface area, and then measuring the specific surface area by the nitrogen adsorption method (BET method) using a specific surface area measuring device (Micromeritic automatic specific surface area measuring device "Flowsorb III2305", manufactured by Shimadzu Corporation). [Preprocessing] (a) The pH of the slurry of component A is adjusted to 2.5±0.1 with an aqueous solution of nitric acid. (b) The slurry of component A, adjusted to pH 2.5±0.1, is placed in a petri dish and dried in a hot air dryer at 150°C for 1 hour. (c) After drying, the obtained sample is finely ground in an agate mortar. (d) The ground sample is suspended in ion-exchanged water at 40°C and filtered through a membrane filter with a pore size of 1 μm. (e) The residue on the filter is washed five times with 20 g of ion-exchanged water (40°C). (f) The filter with the filtrate attached thereto is placed in a petri dish and dried in an atmosphere at 110°C for 4 hours. (g) The dried filtrate (component A) was taken, being careful not to mix in any filter debris, and finely ground in a mortar to obtain a measurement sample.

[0071] (2) Average secondary particle size of silica particles (component A) The average secondary particle diameter (nm) of component A was measured by adding an abrasive to ion-exchanged water so that the concentration of component A was 0.25 mass%, and then placing the resulting aqueous dispersion in a disposable sizing cuvette (a 10 mm polystyrene cell) to a height of 10 mm from the bottom, and using a dynamic light scattering method (apparatus name: Zetasizer Nano ZS, manufactured by Sysmex Corporation).

[0072] (3) Measurement of weight-average molecular weight of water-soluble polymers The weight average molecular weight of the water-soluble polymers (component B, non-component B) was calculated based on peaks in a chromatogram obtained by applying gel permeation chromatography (GPC) under the following conditions. <Measurement conditions for water-soluble polymers> Equipment: HLC-8320 GPC (Tosoh Corporation, detector integrated) Column: α-M + α-M Eluent: 0.15mol / L Na 2 SO 4 ,1%CH 3 COOH / water Flow rate: 1.0mL / min Column temperature: 40℃ Detector: Shodex RI SE-61 differential refractive index detector Standard: Monodisperse polyethylene glycol with known molecular weight

[0073] (4) pKa measurement Using a HM-41K pH meter (Toa DKK Co., Ltd.), an aqueous solution of component B adjusted to 1 M was subjected to potentiometric titration at room temperature with 0.1 M hydrochloric acid. The pKa was calculated from the obtained titration curve.

[0074] (5) Glycidol modification rate The glycidol modification rate is 13 The carbon-carbon NMR spectroscopy was used to determine the <Measurement conditions> Sample: 200 mg of glycidol-modified polyallylamine dissolved in 0.6 mL of heavy water Equipment used: 400MHz 13 C-NMR (Agilent Technologies, Inc. "Agilent 400-MR DD2") Measurement conditions: 13 C-NMR measurement, pulse interval time 5 seconds, tetramethylsilane as standard peak (σ: 0.0 ppm) Accumulation count: 5000 times Each peak range used for integration: A: 71.0 to 72.3 ppm (integral value of the peak of C bound to the secondary hydroxyl group of glycidol reacted with the amino group) B: 32.0 to 41.0 ppm (integrated value of the peak of the main chain C of allylamine) <Glycidol modification rate> The glycidol modification rate (ratio of glycidol equivalents to amino group equivalents) is calculated using the following formula. Glycidol modification rate (equivalent ratio) = 2A / B

[0075] 3. Evaluation of the polishing compositions of Examples 1 to 7 and Comparative Examples 1 and 2 (1) Polishing method etc. Each polishing composition was filtered with a filter (compact cartridge filter "MCP-LX-C10S", manufactured by Advantec Co., Ltd.) immediately before polishing, and the following silicon substrates were subjected to finish polishing and cleaning under the following polishing conditions. <Silicon substrate to be polished> Single crystal silicon substrate [single-sided mirror-finished silicon substrate with a diameter of 200 mm, conductivity type: P, crystal orientation: 100, resistivity: 0.1 Ω·cm or more but less than 100 Ω·cm] The single crystal silicon substrate was previously subjected to rough polishing using a commercially available polishing composition (GLANZOX 1302, manufactured by Fujimi Inc.). After rough polishing, the single crystal silicon substrate was subjected to finish polishing, and had a haze of 2 to 3 ppm.

[0076] <Finish polishing conditions> Polishing machine: Single-sided 8-inch polishing machine "GRIND-X SPP600s" (manufactured by Okamoto Kogyo) Polishing pad: Suede pad (manufactured by Toray Co., Ltd., Asker hardness: 64, thickness: 1.37 mm, nap length: 450 μm, opening diameter: 60 μm) Silicon substrate polishing pressure: 100g / cm 2 Plate rotation speed: 60 rpm Polishing time: 5 minutes Supply rate of polishing composition: 150 g / min Temperature of the polishing composition: 23°C Carrier rotation speed: 62 rpm

[0077] <Measurement of surface roughness (haze) of silicon substrate> The value (DWO haze) measured in a dark field wide oblique incidence channel (DWO) using a surface roughness measuring device "Surfscan SP1-DLS" (KLA Tencor) was used.

[0078] <Cleaning method> After the finish polishing, the silicon substrate was subjected to ozone cleaning and dilute hydrofluoric acid cleaning as described below. In the ozone cleaning, an aqueous solution containing 20 ppm ozone was sprayed from a nozzle at a flow rate of 1 L / min toward the center of the silicon substrate rotating at 600 rpm for 3 minutes. The temperature of the ozone water was kept at room temperature. Next, dilute hydrofluoric acid cleaning was performed. In the dilute hydrofluoric acid cleaning, an aqueous solution containing 0.5 mass% ammonium hydrogen fluoride (special grade, Nacalai Tesque, Inc.) was sprayed from a nozzle at a flow rate of 1 L / min toward the center of the silicon substrate rotating at 600 rpm for 6 seconds. The above ozone cleaning and dilute hydrofluoric acid cleaning were performed as one set, for a total of two sets, and finally spin drying was performed. In the spin drying, the silicon substrate was rotated at 1,500 rpm.

[0079] (2) Evaluation of polishing speed The weight of each silicon substrate before and after polishing was measured using a precision balance ("BP-210S" manufactured by Sartorius), and the weight difference obtained was divided by the density, area and polishing time of the silicon substrate to obtain the single-sided polishing rate per unit time. The results are shown in Table 1. The weight of the silicon substrate after polishing refers to the weight of the silicon substrate after the above-mentioned finish polishing and cleaning were performed.

[0080] (3) Evaluation of storage stability of concentrate 100 g of each polishing composition concentrate was placed in a 100 ml screw tube and sealed, and the storage stability after one day was evaluated according to the following evaluation criteria. The polishing composition concentrate was stored in a room at 23° C. The results are shown in Table 1. <Evaluation criteria> A: One day after the preparation of the concentrated polishing composition, no agglomeration or separation occurs and the dispersion stability is maintained. B: One day after the preparation of the concentrated polishing composition, slight agglomerations and separation were observed. C: Aggregates and separation were observed one day after the concentrated polishing composition was prepared.

[0081] [Table 1]

[0082] As shown in Table 1, it was found that the polishing compositions of Examples 1 to 7 were able to achieve both an improved removal rate and good storage stability of the concentrate, as compared to the polishing compositions of Comparative Examples 1 and 2.

[0083] 4. Evaluation of the polishing compositions of Examples 8 to 9 and Comparative Example 3 (1) Polishing method Each polishing composition was filtered using a filter (compact cartridge filter "MCP-LX-C10S", manufactured by Advantech) immediately before polishing, and the following silicon substrates were polished under the same polishing conditions as in 3(1) above, and then washed using the same washing method as in 3(1) above. <Silicon substrate to be polished> A polysilicon substrate [a 200 mm diameter silicon single-sided mirror substrate (conductivity type: P, crystal orientation: 100, resistivity: 0.1 Ω cm or more, but less than 100 Ω cm)] was deposited on the substrate by plasma CVD. 2 A 4400 Å thick silicon film was then deposited on the substrate by plasma CVD.

[0084] (2) Evaluation of polishing speed The polishing rate was evaluated using a polysilicon substrate as the substrate to be polished in the same manner as in 3(2) above. The results are shown in Table 2.

[0085] (3) Evaluation of storage stability of concentrate The storage stability of the concentrate was evaluated in the same manner as in 3(3) above. The results are shown in Table 2.

[0086] [Table 2]

[0087] As shown in Table 2, it was found that, compared to the polishing composition of Comparative Example 3, the polishing compositions of Examples 8 and 9 were able to achieve both an improved removal rate and good storage stability of the concentrate. [Industrial Applicability]

[0088] The polishing composition of the present disclosure can achieve both improved polishing rate and storage stability. Therefore, the polishing composition of the present disclosure is useful as a polishing composition used in the manufacturing process of various semiconductor substrates, and is particularly useful as a polishing composition for finish polishing of silicon substrates.

Claims

1. Contains the following component A and the following component B, A polishing composition for silicon substrates, having a pH of more than 8.5 and not more than 14. Component A: Silica particles Component B: an amino group-containing water-soluble polymer having a pKa of 5 or more and 8.5 or less

2. The polishing composition according to claim 1 , wherein Component B contains structural units derived from one or more monomers selected from allylamine and diallylamine.

3. The polishing composition according to claim 2 , wherein at least a portion of the amino groups in the structural units derived from allylamine have a sterically shielding group.

4. 4. The polishing composition according to claim 2, wherein at least a part of the amino groups in the structural units derived from allylamine is a secondary amino group or a tertiary amino group containing a hydrocarbon group having 3 to 11 carbon atoms and a hydroxyl group.

5. 5. The polishing composition according to claim 1, wherein Component B is a reaction product of a polyallylamine and a glycidol derivative.

6. The polishing composition according to claim 2 , wherein at least a portion of the amino groups in the constitutional units derived from diallylamine have an electron-withdrawing group at the β-position or the γ-position.

7. 7. The polishing composition according to claim 1, wherein Component B is a compound containing a structural unit represented by the following formula (III): [Formula 1] In formula (III), R 3 represents an alkyl group having 1 to 3 carbon atoms which may have a hydroxyl group, and n+m=1.

8. A method for polishing a silicon substrate, comprising the step of polishing a silicon substrate to be polished with the polishing composition according to claim 1 .

9. 9. The polishing method according to claim 8, wherein the silicon substrate to be polished is a single crystal silicon substrate or a polysilicon substrate.

10. A step of polishing a silicon substrate to be polished using the polishing composition according to any one of claims 1 to 7; and cleaning the polished silicon substrate.

Citation Information

Patent Citations

  • Polishing composition

    JP2008252022A

  • Polishing liquid, polishing liquid set, and substrate polishing method

    JP2017139350A

  • Polishing composition, and polishing method and substrate production method using same

    WO2013084686A1

  • Composition for grinding, and method for grinding silicon substrate

    WO2016143323A1